Physical and Mechanical Properties of Particleboard from Petung Bamboo-waste using Eco-friendly Chitosan-starch Adhesive - Dwiyanna, Riska; Widyorini, Ragil; Dewi, Greitta Kusuma (Masyarakat Peneliti Kayu Indonesia, 2023)
The effect of starch addition in chitosan adhesive on the physical and mechanical properties of petung bamboo particleboard from bamboo-sawing waste was investigated in this work. The utilization of bamboo-sawing waste particles as a raw material for particle board manufacturing has been gaining attention due to its waste reduction potential and economic advantages. The results of this study indicated that starch has been proven to enhance the physical and mechanical properties of petung bamboo particleboard. Adding only 4% wt. of chitosan/starch adhesive with a chitosan/starch ratio of 7/3 (w/w) has resulted in an improvement in the physical properties of the particleboard, such as moisture content, thickness swelling, and water absorption. It has also enhanced the mechanical properties of the particle board, including modulus of elasticity (MOE), modulus of rupture (MOR), and internal bonding (IB), in comparison to chitosan adhesive without starch addition. Overall, these findings provide insights for further developing chitosan/starch adhesive, especially to produce natural-based adhesives with good bonding quality.